(untitled) (World Economics and Finance Bulletin, 2026)
The research aims to determine the appropriate methods for analyzing environmental costs and showing the importance of this in implementing the strategy of environmental efficiency and protecting the environment from pollution to help provide information on environmental costs and on the efforts and amounts spent to protect the environment and to reach accurate results that show the extent of the company’s success in achieving its environmental goals. Activity-based costing was used to examine the environmental costs in the Karbala Cement Factory, one of Southern Cement Company’s operations, using data from the fiscal year 2022. The study came to a number of results, the most significant of which was that environmental costs might be analyzed using the costing technique based on laboratory operations, or the research sample. Also, analyzing environmental costs in this way can help implement the environmental efficiency strategy and provide information on environmental costs and on the efforts and amounts spent to protect Environment and reaching accurate results that show the extent of success in achieving environmental goals.